Kedudukan Mahkamah Konstitusi Dalam Menjaga Hak Konstitusional Warga Negara - Sugianto, Bambang; Arista, Windi; Amin, Muhammad Nur (Lex Stricta : Jurnal Ilmu Hukum, 2026)
The Constitutional Court is a state institution established after the amendment of the 1945 Constitution as a manifestation of the principles of the rule of law and constitutional supremacy. This institution has a strategic role in safeguarding and protecting the constitutional rights of citizens, particularly through its authority to review laws against the 1945 Constitution. This study aims to analyze the position of the Constitutional Court in the Indonesian constitutional system and its role in protecting the constitutional rights of citizens. The research method used is normative legal research with a legislative and conceptual approach. The results show that the Constitutional Court acts as the guardian of the constitution and the final interpreter of the constitution with final and binding decisions. Through the judicial review mechanism, the Constitutional Court functions as an important instrument in ensuring constitutional supremacy, strengthening the rule of law, and protecting the constitutional rights of citizens in Indonesia's constitutional democracy system.